2013
DOI: 10.1002/jgrb.50088
|View full text |Cite
|
Sign up to set email alerts
|

Temporal changes in attenuation associated with the 2004 M6.0 Parkfield earthquake

Abstract: Elevated seismic attenuation is often observed in fault zones due to the high degree of fracturing and fluid content. However, temporal changes in attenuation at the time of an earthquake are poorly constrained but can give indications of fracture damage and healing. In this study, spectral ratios between earthquakes within repeating clusters are calculated in an attempt to resolve temporal variations in attenuation at the time of the 2004 M6.0 Parkfield earthquake. A sharp increase in attenuation is observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 72 publications
1
41
3
Order By: Relevance
“…It is well known that permeability increases in fault zones after seismic events, when preferential flow paths are enhanced or newly created [Cox et al, 2014;Kitagawa et al, 2007;Wang and Manga, 2010]. Within a few years or decades, permeability progressively returns to the preseismic conditions due to mineralization of the fractures [Brenguier et al, 2008;Kelly et al, 2013]. The available data set is rich for all PGA classes down to at least 1000 m depth ( Figure S8).…”
Section: Geological Provinces and Seismotectonic Activity As Main Facmentioning
confidence: 99%
“…It is well known that permeability increases in fault zones after seismic events, when preferential flow paths are enhanced or newly created [Cox et al, 2014;Kitagawa et al, 2007;Wang and Manga, 2010]. Within a few years or decades, permeability progressively returns to the preseismic conditions due to mineralization of the fractures [Brenguier et al, 2008;Kelly et al, 2013]. The available data set is rich for all PGA classes down to at least 1000 m depth ( Figure S8).…”
Section: Geological Provinces and Seismotectonic Activity As Main Facmentioning
confidence: 99%
“…Following the 2004 M 6 Parkfield earthquake, the recurrence times of these clusters significantly decreased, and then gradually increased, but with minimal change in moment [ Chen et al, ]. Allmann and Shearer [] and Kelly et al [] found both attenuation and earthquake stress drop to change along the fault following the M 6 earthquake. My aims are twofold.…”
Section: Introductionmentioning
confidence: 99%
“…For completeness, we also use the P‐wave arrival, either the rotated component or a stack of all three components, as performed by Kelly et al . (). First, we use every event as a reference.…”
Section: Changes In Anisotropic Attenuation With Timementioning
confidence: 97%
“…Kelly et al . () observed temporal variations in P‐wave attenuation before and after the 2004 M6.0 Parkfield earthquake. They attributed this variation to fracture dilatancy due to changes in stress conditions and fluid pressure before and after the earthquake.…”
Section: Introductionmentioning
confidence: 99%